2020
DOI: 10.1007/s40685-019-00107-8
|View full text |Cite
|
Sign up to set email alerts
|

Observational learning and willingness to pay in equity crowdfunding

Abstract: This study examines interdependencies between investments of equity crowdfunders. Based on hand-collected data from a well-established equitycrowdfunding platform, we find strong indication that investors observe previous investments to determine their willingness to pay for equity shares. Furthermore, the investment behavior of predecessors may lead investors to deviate from average investment behavior. In particular, investors are willing to pay more than the average investment, when the focal campaign is ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 50 publications
2
5
1
Order By: Relevance
“…Second, the number of large investments during a campaign appears to have a negative effect on startup survival. This contradicts the positive effect of large investments on the number of investments and their size on Companisto (Hornuf and Schwienbacher 2018;Walther and Bade 2020). Our finding indicates that large investments might have led to information cascades and consequently, inefficient investments.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Second, the number of large investments during a campaign appears to have a negative effect on startup survival. This contradicts the positive effect of large investments on the number of investments and their size on Companisto (Hornuf and Schwienbacher 2018;Walther and Bade 2020). Our finding indicates that large investments might have led to information cascades and consequently, inefficient investments.…”
Section: Discussioncontrasting
confidence: 94%
“…In this context, Hornuf and Schwienbacher (2018) demonstrate that large investment amounts and positive comments lead to a larger number of investments in the days following such investments and comments. Similarly, Walther and Bade (2020) show that large investments in the campaign increase investors' willingness to pay.…”
Section: Offering and Post-offering Successmentioning
confidence: 98%
See 2 more Smart Citations
“…Walther and Bade (2020) analyzed ECF projects in Europe and found that “hot” campaigns with “large investors” attracted significantly greater funding. These campaigns were analyzed from the viewpoints of (1) geographical factors, (2) word-of-mouth and (3) risk factors.…”
Section: Prior Researchmentioning
confidence: 99%